2010
DOI: 10.1111/j.1365-2702.2010.03282.x
|View full text |Cite
|
Sign up to set email alerts
|

Models to enhance research capacity and capability in clinical nurses: a narrative review

Abstract: To build research capability and capacity in clinical nurses, there is a need to evaluate models and determine the best approach that will provide clinical nurses with research opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 29 publications
2
89
0
Order By: Relevance
“…While there is an identified inconsistency in the meaning of the term research capacity building, within this paper it refers to involvement at all levels of the research process from question design to dissemination [5, 8]. Research capacity building has been identified as a priority in nursing research and development [5, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is an identified inconsistency in the meaning of the term research capacity building, within this paper it refers to involvement at all levels of the research process from question design to dissemination [5, 8]. Research capacity building has been identified as a priority in nursing research and development [5, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Strong leadership has long been advocated as a key element in clinical research capacity building [8, 10, 21, 22, 24]. Other features that reflect a strong leadership presence include, the development of a strategy, formalising research policies and support [8, 20, 24, 25], identifying priorities [24], the development of a research culture [15, 20, 22], an organisational need for research [8] and the use of a steering committee [11, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…O'Byrne and Smith [30] identified three models to build research capacity in clinical nurses: the Evidence-Based Practice model, Facilitative model, and Experiential Learning model. Despite using various definitions of research competencies, all of these models focus on developing nurses' skills to conduct research and to appraise, synthesize, and implement research findings [31][32][33].Building research capacity for nurses [13] increases nurses' confidence [34] and quality in providing care [35].…”
Section: Research Capacity Building For Nursesmentioning
confidence: 99%
“…12 The main sources of information used in this review to identify the models were a book, a thesis of Full Professors 14 and seven scientific articles. 2,[15][16][17][18][19][20] After the identification of the models, a search of specific references on the topic of interest was performed and the published articles were read. The models for the use of research in practice were presented according to the historical emergence.…”
Section: Methodsmentioning
confidence: 99%